2021
DOI: 10.3390/ijerph18116054
|View full text |Cite
|
Sign up to set email alerts
|

Association between Psychosocial Factors and Oral Symptoms among Residents in Fukushima after the Great East Japan Earthquake: A Cross-Sectional Study from the Fukushima Health Management Survey

Abstract: Oral health is closely related to subjective general health and systemic diseases. This cross-sectional study aimed to identify the factors related to oral symptoms and their worsening in relation to psychosocial factors after the Great East Japan Earthquake. In this study, 64,186 residents aged 15–101 years old, who experienced the earthquake on 11 March 2011, were surveyed regarding their oral symptoms; psychological factors, such as post-traumatic reactions and psychological distress; and social factors suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…As a post-hoc analysis, we also considered studies describing oral health status among people in the context of a natural disaster, without reporting a specific intervention. We found 5 studies, [44][45][46][47][48] of which the reported outcomes were maxillofacial injuries, tooth loss, periodontal diseases, and temporomandibular disorders. Overall, most studies found that the changes caused by an earthquake such as deteriorating socioeconomic circumstances (for example, housing damage or temporary housing) appeared to impair oral health care practice, oral hygiene habits, and nutritional intake, among others.…”
Section: Resultsmentioning
confidence: 99%
“…As a post-hoc analysis, we also considered studies describing oral health status among people in the context of a natural disaster, without reporting a specific intervention. We found 5 studies, [44][45][46][47][48] of which the reported outcomes were maxillofacial injuries, tooth loss, periodontal diseases, and temporomandibular disorders. Overall, most studies found that the changes caused by an earthquake such as deteriorating socioeconomic circumstances (for example, housing damage or temporary housing) appeared to impair oral health care practice, oral hygiene habits, and nutritional intake, among others.…”
Section: Resultsmentioning
confidence: 99%